2018
DOI: 10.1002/jclp.22660
|View full text |Cite
|
Sign up to set email alerts
|

Sources of moral injury among war veterans: A qualitative evaluation

Abstract: Implications for the further development of the moral injury construct and treatment are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 25 publications
(57 reference statements)
5
56
1
Order By: Relevance
“…Our preliminary findings suggest that social isolation may be a form of self‐punishment for self‐based PMIEs whereas isolation may be a form of self‐protection for other‐based PMIEs. In a recent qualitative study of war veterans, Schorr and colleagues () also found similar fine‐grained distinctions between the impact of self‐ and other‐based PMIEs, which may be validated upon completion of Phase I data collection.…”
Section: Discussionmentioning
confidence: 75%
“…Our preliminary findings suggest that social isolation may be a form of self‐punishment for self‐based PMIEs whereas isolation may be a form of self‐protection for other‐based PMIEs. In a recent qualitative study of war veterans, Schorr and colleagues () also found similar fine‐grained distinctions between the impact of self‐ and other‐based PMIEs, which may be validated upon completion of Phase I data collection.…”
Section: Discussionmentioning
confidence: 75%
“…Notwithstanding this, MI is often theorized as resulting in shame, guilt, distrust, anger, grief, turmoil with God or a higher power, self‐condemnation, and disgust (Bryan et al ; Currier et al ; Jinkerson ; Litz et al ; Shay ). MI can be self‐directed (individual perpetrated an act that led to a transgression of moral boundaries) or other directed (witnessing or hearing about a transgression; Schorr et al ) and is linked with suicidality (suicidal ideation, plans, behaviour, and/or attempt) in veterans (Bryan et al ; ). MI represents an existential set of issues spanning psychological behavioural, spiritual, and interpersonal from an actual or perceived violation of one's moral beliefs (Jinkerson ) resulting in a profound ‘moral disorientation’ (Molendijk , p. 6) in other words ‘the loss of one's moral frame of reference and one's moral self‐perception’ (Molendijk , p. 6).…”
Section: About Moral Injurymentioning
confidence: 99%
“…Leadership betrayal reflects a breach of trust in systems of authority and responsibility over and above interpersonal violations (Schorr et al . 2018; Smith & Freyd 2017). Shay’s (1994) seminal literature on moral injury also identified leadership failings that amounted to betrayal within the structure of command as a core construct.…”
Section: Antecedentsmentioning
confidence: 99%